Optimal Design of Air Separation Plants with Variable Electricity Pricing - Pattison, Richard C.; Baldea, Michael (Computer Aided Chemical Engineering, 2014)
Air separation processes are significant electricity consumers. Operating air separation units (ASUs) at variable capacity can be economically beneficial (in time varying electricity price scenarios) and can serve as a means for mitigating grid load during peak times. Process design should thus account for such operational fluctuations. In this paper, we study the optimal design of ASUs assumed to be operating at variable capacity under variable electricity price. We introduce a novel pseudo-transient equation-oriented framework for process modelling, and use the developed models together with a time relaxation-based optimization algorithm to optimize the design of the plant subject to a time-of-day price scenario.